⎩ ⎪ ⎨ ⎪ ⎧ x 3 + ( y − 9 ) 3 x + ( y − 9 ) x 2 + ( y − 9 ) 2 = 6 8 5 9 = 1 9 = 3 6 1
Let the two solutions of ( x , y ) satisfying the system of equations above be ( x 1 , y 1 ) , ( x 2 , y 2 ) . Give your answer as x 1 + x 2 + y 1 + y 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let z = y − 9 . Then we have x + z = 1 9 and:
x 2 + z 2 ( x + z ) 2 − 2 x z 1 9 2 − 2 x z 3 6 1 − 2 x z ⟹ x z x ( y − 9 ) = 3 6 1 = 3 6 1 = 3 6 1 = 3 6 1 = 0 = 0
⟹ { x 1 = 0 y 2 = 9 ⟹ 0 + y 1 − 9 = 1 9 ⟹ x 2 + 0 = 1 9 ⟹ y 1 = 2 8 ⟹ x 2 = 1 9
Therefore x 1 + y 1 + x 2 + y 2 = 0 + 2 8 + 1 9 + 9 = 5 6 .
Note: x 3 + z 3 = ( x + z ) ( x 2 − x z + z 2 ) = ( x + z ) ( x 2 + z 2 ) = ( x + z ) 3 = 1 9 3 = 6 8 5 9
How do I mention you, @Chew-Seong Cheong? It's really hard...
The equations are :
x + ( y − 9 ) = 1 9
x 2 + ( y − 9 ) 2 = 1 9 2
x 3 + ( y − 9 ) 3 = 1 9 3 .
Solutions to these equations are
x = 0 , y − 9 = 1 9 ⟹ y = 2 8
y − 9 = 0 ⟹ y = 9 , x = 1 9 .
So, x 1 = 0 , x 2 = 1 9 , y 1 = 2 8 , y 2 = 9
⟹ x 1 + x 2 + y 1 + y 2 = 5 6 .
@Alak Bhattacharya , can you show how you got these solutions, please?
Log in to reply
Probably by inspection. I did that too.
See Chew-Seong's solution.
Problem Loading...
Note Loading...
Set Loading...
For first pair x 1 , y 1 ,
x 1 + y 1 − 9 ⟹ x 1 + y 1 = 1 9 = 2 8
For second pair x 2 , y 2 ,
x 2 + y 2 − 9 ⟹ x 2 + y 2 = 1 9 = 2 8
Other equations are just for finding values, which we don't need to.